Communication Interaction Of Double Burden Batak Women In Patriarkhi Family In Gender Analysis In North Sumatra - Nursapia Harahap (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
Study aim for knowing how interaction social  family  woman batak double burden in a patrilineal culture a gender analysis . Study this conducted with approach qualitative descriptive , collecting data with observation and interview to woman special double burden hobo woman scavenger , interaction social with children , husband and environment . This study is supported theory interactionalist Symbolic Herbert Blumer and the Hierarchy from Abraham Maslow . Research results show that woman working hobo _ as scavengers in system kinship patriarchy is bone back family Beside function reproduction , care child , serve husband and take care house stairs . Woman trying for Fulfill  needs house stairs , education child children and social _ Attitude independent and work hard supported by existence expression culture " my son " hamoraon , hagabeon hasangapon in au ” make woman fight hard even though treatment husband no protect family. Work hard wife no considered husband as a advantages proper woman _ to be appreciated rather on the contrary man man feel stepped on price herself because wife taking over not quite enough answer house ladder because traditional batak man man is "King". There is an anomaly that appears where husband which no occupy function gendered will _ agreed custom customs no considered gender deviation . Condition this cause crisis integration Among husband and wife so that harmony house ladder start eroded . Different with attitude child child to parents , children the child is very obedient and respectful to his father and mother even though not quite enough answer family it 's on the shoulder mother . Relation social and interaction that is built very closely and well , raises attitude of love dear , cheer up high learning , responsibility _ responsibility , cooperation and mutual help Among child  constructed by conditions double burden mother .